A Comparison of Factors Influencing Health Risk Behaviour of College Students in the Countries of the Carpathian Basin - Kovács, Klára (European Journal of Mental Health, 2018)
An examination of the health behaviour of college students is important from several aspects. First, starting and continuing studies, being detached from the family and friends creates a new situation for students (Greene et al. 2001), the decreasing parental control may test the development of self-regulation in a young person. The chances of harmful forms of behaviour, especially binge drinking, increase among students (Von Ah et al. 2004; Hunt & Eisenberg 2010; O’Malley & Johnston 2002). In our study, we intended to find out how individual and socio-economic factors influence the health risk behaviour (smoking, excessive use of alcohol, and drugs) of higher-education students in Central and Eastern European countries. For the analyses, we used a database of the Centre for Higher Education Research and Development (CHERD-H), including the higher education institutions in the border regions of five countries: Hungary, Slovakia, Ukraine, Romania and Serbia (IESA 2015, N = 2,017). Our results show that although the regions concerned share similar historical and cultural traditions, there are different factors influencing the health behaviour of students in the countries concerned. In general, we may state that, with the exception of Serbia, health risk behaviour is more characteristic of male students than of female ones. It is only in Hungary that subjective financial situations play a role in the health-risk behaviour of students in Hungary. The social-partying way of life is a risk factor in almost all the regions concerned. Recreational activity is a protective factor in Hungary against substance use, just as much as sports among the Subcarpathian students. Being familiar with the meaning of life is a protective factor for the students in the Partium and Transylvania. The level and different dimension of individual trust has an inconsistent influence in the specific countries.